Dietary Compounds as Epigenetic Modulating Agents in Cancer - Carlos-Reyes, Ángeles; López-González, José Sullivan; Meneses-Flores, Manuel; Gallardo-Rincón, Dolores; Ruíz-García, Erika; Marchat, Laurence A.; Astudillo-de la Vega, Horacio; Hernández de la Cruz, Olga N.; López-Camarillo, César (Frontiers in Genetics, 2019)
Epigenetic mechanisms controls gene expression during normal development and their aberrant regulation may leads to human diseases including cancer. Complementary therapies based on natural phytochemicals can largely modulate mammalian epigenome through modifications of proteins responsible for chromatin remodeling. Phytochemicals are present in fruits, seeds and vegetables as well as in foods supplements and they acts as powerful cellular antioxidants. Several dietary compounds such as green tea, curcumin, genistein, quercetin and resveratrol exhibit potent antitumor activities through the reversion of the epigenetic alterations responsible for the activation of oncogenes and inactivation tumor suppressor genes occurring in the early stages of tumorigenesis. In this review, we summarize the actual knowledge about the role of dietary polyphenols in the restoration of aberrant epigenetic alterations with a particular focus in DNA methylation and histone modifications. Furthermore, we will discuss the mechanisms through these natural compounds modulate gene expression at epigenetic level and their molecular targets described in diverse types of cancer. The modulation of the epigenetic activity by natural compounds will allow the development of novel biomarkers for cancer prevention, and its potential utilization in combination with standard chemotherapy could represents an attractive alternative approach in cancer therapies.